LATE-PLEISTOCENE SEISMITES FROM LAKE ISSYK-KUL, THE TIEN SHAN RANGE, KYRGHYZSTAN - Bowman D.; Korjenkov A.; Porat N. (My University, 2004)
The aim of the study is to record the occurrence of sediment deformation structures in one of the tectonically most active areas on the globe, the Tien Shan range in Central Asia and to examine the significance of the deformations as indicators of palaeoseismicity.Soft-sediment deformation structures in form of balls and pseudo-nodules are exposed in the Issyk-Kul basin, within interfingering beds of shallow lacustrine, beach and fluviatile origin. Additional deformation structures that were encountered are: a complex and chaotic folded structure, giant balls and a “pillar” structure which has not been previously reported, where marl intrudes down into coarse pebbley sand and forms pillar morphology. Liquefaction features and bedforms related to storm and breaking waves were not encountered. Neither was there evidence of turbidites. Seven field criteria for relating soft-sediment deformation to palaeoseismic triggering provide strong evidence for a seismic origin of the deformation structures. Empirical relationships between magnitude and the maximum distance from an epicenter to liquefaction sites make the active epicentral zone north of Lake Issyk-Kul, with its frequent high magnitude events, the most favorable source for the deformation structures. Luminescence dating of the sediments gives a time window of 26±2.1 to 10.5±0.7 ka BP, indicating latest Pleistocene seismic activity.
Keywords: Neotectonics; Seismites; Palaeoseismicity; Soft-sediment deformation; Tien Shan; Kyrghyzstan; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен